Deep Hydrodesulphurization Via Hydrogen Spillover - Gil-Llambias, F (Kluwer Academic Publishers, 2011)
The synergistic effect between Co//Mo and Co//W stacked bed systems in the hydrodesulphurization (HDS) of 4,6-dimethyldibenzothiophene (4,6-DMDBT) was studied. The reaction was carried out in a high-pressure continuous-flow microreactor at 3 MPa and 300 °C. The observed synergism can only be explained by the action of hydrogen spillover (HSO). The selectivity in hydrogenation over direct desulphurization pathways (HYD/DDS) of Mo/?-Al2O3 and W/?-Al2O3 catalysts increased when the reaction was carried out in Co//Mo and Co//W stacked bed systems, respectively. The changes in selectivity can be explained by the fact that hydrogen spillover does not only create more active sites, but it also modifies the sites, favouring the HYD pathway. Differences in synergistic effect between Co//Mo and Co//W stacked bed systems were related to the higher degree of sulphurization of the molybdenum compared to the tungsten phase, as detected by XPS. Graphical Abstract: [Figure not available: see fulltext.] © 2011 Springer Science+Business Media, LLC.